Effects of the benzoxazole group on green fluorescent protein chromophore crystal structure and solid state photophysics - Ghodbane, Abdelhamid; Fellows, W. Brett; Bright, John R.; Ghosh, Debashree; Saffon, Nathalie; Tolbert, Laren M.; Fery-Forgues, Suzanne; Solntsev, Kyril M. (Journal of Materials Chemistry C, 2016)
Four benzoxazole-substituted GFP chromophores that differ by the length of their alkyl chain (from C1 to C12) were synthesized. In solution, the four compounds showed identical spectroscopic behavior, emitting blue light with moderate quantum yield. In the solid state, the butyl, pentyl and dodecyl derivatives strongly emitted orange light, while the methyl derivative was only weakly emissive. Based on the X-ray data and DFT calculations, emission in the solid state was explained by the formation of excimers. A very unusual ``hot-dog''-type excimer was found for the dodecyl derivative, in which two overlapping chromophores are separated by an alkyl chain.